Nonlinear analysis and simulation of active hybrid aerodynamic and aerostatic bearing system. Issue 3 (December 2019) - Wang, Cheng-Chi; Lee, Rong-Mao; Yau, Her-Terng; Lee, Tsui-Er
Active hybrid aerodynamic and aerostatic bearing system has gradually become more valued in recent years for its application in the precision machine field, especially for precision instruments and mechanisms that require high rotational speed, high precision, and high rigidity support. In this system, air lubricated bearing is mainly used for support. Although the carrying capacity is not as high as oil film bearings, air lubricated bearings can provide a work environment where the rotor (spindle) will not experience axial deformation at high rotational speed and low heat generation. In practice, spindle system dynamic problems include critical speed, spindle imbalance, and improper bearing design, which can cause the spindle system to produce aperiodic motion, instability, and even chaotic motion under certain parameters and conditions during its operation. If severe, these irregular motions may cause machine damage or delay production. In order to understand what type of work situation can produce aperiodic phenomenon, and to prevent irregular vibration and reduce instantaneous air hammer effect, the finite difference method and mixed method are used to explore the related characteristics for spindle system. Meanwhile, relevant theories including bifurcation diagram, Poincare map, spectrum response phenomenon, and maximum Lyapunov exponents are applied to analyze rotor non-linear dynamic behavior. In addition, we verified the non-linear motion parameter conditions to prevent spindle system from falling into the instable status during design. The objective is to lower the probability of chaotic phenomenon in the system and reduce damage caused by irregular vibrations in the system. The result of this study can serve as a reference when designing precision spindle systems or mechanisms.